2021
DOI: 10.1016/j.scs.2021.103170
|View full text |Cite
|
Sign up to set email alerts
|

Air quality during three covid-19 lockdown phases: AQI, PM2.5 and NO2 assessment in cities with more than 1 million inhabitants

Abstract: Implemented quarantine due to the ongoing novel coronavirus (agent of COVID-19) has an immense impact on human mobility and economic activities as well as on air quality. Since then, and due to the drastic reduction in pollution levels in cities across the world, a large discussion has been magnetized regarding if the lockdown is an adequate alternative counter-measure for enhancing air quality. This paper aimed at studying the Air Quality Index (AQI), PM2.5, and tropospheric NO2 levels in three lockdown phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(57 citation statements)
references
References 61 publications
5
41
0
1
Order By: Relevance
“…Such a trend was also reported Rodríguez-Urrego and Rodríguez-Urrego (2020) , who concluded that air quality in Jakarta worsened due to the lockdown. Benchrif et al (2021) noted that a remarkable increase in PM2.5 concentration despite the lockdown measure. They attributed the increase due to the mobility of vehicles that remained in operation during the pandemic and to using private vehicles instead of public transportation.…”
Section: Calculating Changes Using Pre and During Lockdown Valuesmentioning
confidence: 99%
“…Such a trend was also reported Rodríguez-Urrego and Rodríguez-Urrego (2020) , who concluded that air quality in Jakarta worsened due to the lockdown. Benchrif et al (2021) noted that a remarkable increase in PM2.5 concentration despite the lockdown measure. They attributed the increase due to the mobility of vehicles that remained in operation during the pandemic and to using private vehicles instead of public transportation.…”
Section: Calculating Changes Using Pre and During Lockdown Valuesmentioning
confidence: 99%
“…Thus, these activities’ behaviour can be extrapolated from the analysis of changes in the emissions of pollutants. On this behalf, Benchrif et al (2021) summarized the most recent studies addressing the evolution of air pollutants during the pandemic, concluding that the lockdown lead to a drastic reduction of air pollution levels at the cost of the normal functioning of urban activity, including road traffic and industry. Likewise, Wang & Li (2021) looked at the non-linear relationship between the impact of the COVID-19 lockdown and four pollutants in eight cities worldwide (Wuhan, New York, Milan, Madrid, Bandra, London, Tokyo and Mexico City), showing that the global lockdown reduced concentrations of NO 2 in these cities, up to 50% during 2020.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although many studies have reported the effects of COVID-19 lockdown on the air pollution in many cities in China, studies on Sichuan province or southwest China are fewer. At the same time, those studies on Sichuan province that have been conducted mainly focused on the variations in air pollution indexes (PM 2.5 , PM 10 , SO 2 , NO 2 , CO and O 3 ) before and during the lockdown period ( Benchrif et al, 2021 ; Deng et al, 2021 ; Fan et al, 2021 ; Wang et al, 2020c ; Zhang et al, 2020 ), and there is almost no in-depth research on the chemical composition, source and pollution formation mechanism of particulate matter. Therefore, in order to obtain more information about the effects of the COVID-19 lockdown on air pollution in southwest China, single particle aerosol mass spectrometer (SPAMS) observations, as well as those from other types of online observation equipments, were used to measure the atmospheric single aerosol particles and gaseous pollutants in Chengdu, the capital city of Sichuan province, before and during the lockdown period.…”
Section: Introductionmentioning
confidence: 99%